Effects of a school readiness intervention on hypothalamus–pituitary–adrenal axis functioning and school adjustment for children in foster care. (18th September 2017) - Graham, Alice M.; Pears, Katherine C.; Kim, Hyoun K.; Bruce, Jacqueline; Fisher, Philip A.
Abstract: Maltreated children in foster care are at high risk for dysregulated hypothalamus–pituitary–adrenal (HPA) axis functioning and educational difficulties. The present study examined the effects of a short-term school readiness intervention on HPA axis functioning in response to the start of kindergarten, a critical transition marking entry to formal schooling, and whether altered HPA axis functioning influenced children's school adjustment. Compared to a foster care comparison group, children in the intervention group showed a steeper diurnal cortisol slope on the first day of school, a pattern previously observed among nonmaltreated children. A steeper first day of school diurnal cortisol slope predicted teacher ratings of better school adjustment (i.e., academic performance, appropriate classroom behaviors, and engagement in learning) in the fall of kindergarten. Furthermore, the children's HPA axis response to the start of school mediated the effect of the intervention on school adjustment. These findings support the potential for ameliorative effects of interventions targeting critical transitional periods, such as the transition of formal schooling. This school readiness intervention appears to influence stress neurobiology, which in turn facilitates positive engagement with the school environment and better school adjustment in children who have experienced significant early adversity.